MODELLING AND OPTIMIZATION OF PORTABLE SUPERVISION THE DEVICE OF BY MEANS OF ANALYSIS OF RIGIDITY OF ITS DESIGN IN THE ENVIRONMENT OF Pro/ENGINEER SAPR - R. V. Feodortsau; A. V. Fufaev; A. A. Bolotin (Приборы и методы измерений)
The 3D model of the portable device of supervision using SAPR Pro/ENGINEER is constructed. By means of the module of the engineering analysis built in this package the mechanical analysis of rigidity of a product design is carried out. Own frequency fluctuations of a product by orthogonal axes and the corresponding points of the maximal tension concentration in optical and mechanical components under the influence of their gravity are determined.